The ABC Transporter ABCG1 Is Required for Suberin Formation in Potato Tuber Periderm. Issue 8 (8th August 2014) - Landgraf, Ramona; Smolka, Ulrike; Altmann, Simone; Eschen-Lippold, Lennart; Senning, Melanie; Sonnewald, Sophia; Weigel, Benjamin; Frolova, Nadezhda; Strehmel, Nadine; Hause, Gerd; Scheel, Dierk; Böttcher, Christoph; et al.
Abstract : The water barrier function of potato tuber skin depends on the polyester suberin and associated waxes. Here, a transporter was identified that is required for the formation of suberin in potato tuber periderm; potato plants lacking this transporter give rise to tubers that are more prone to water loss. Abstract: The lipid biopolymer suberin plays a major role as a barrier both at plant-environment interfaces and in internal tissues, restricting water and nutrient transport. In potato ( Solanum tuberosum ), tuber integrity is dependent on suberized periderm. Using microarray analyses, we identified ABCG1, encoding an ABC transporter, as a gene responsive to the pathogen-associated molecular pattern Pep-13. Further analyses revealed that ABCG1 is expressed in roots and tuber periderm, as well as in wounded leaves. Transgenic ABCG1- RNAi potato plants with downregulated expression of ABCG1 display major alterations in both root and tuber morphology, whereas the aerial part of the ABCG1- RNAi plants appear normal. The tuber periderm and root exodermis show reduced suberin staining and disorganized cell layers. Metabolite analyses revealed reduction of esterified suberin components and hyperaccumulation of putative suberin precursors in the tuber periderm of RNA interference plants, suggesting that ABCG1 is required for the export of suberin components.